2020
DOI: 10.20870/productions-animales.2013.26.2.3146
|View full text |Cite
|
Sign up to set email alerts
|

Maîtrise par l’alimentation des teneurs en acides gras et en composés vitaminiques du lait de vache

Abstract: Maîtrise par l'alimentation des teneurs en acides gras et en composés vitaminiques du lait de vacheLa composition en acides gras et en vitamines du lait de vache a un rôle prépondérant pour sa qualité nutritionnelle. Cet article présente les principaux facteurs alimentaires influençant leurs teneurs. Maîtrise par l'alimentation des teneurs en acides gras et en composés vitaminiques du lait de vache / 191 INRA Productions Animales, 2013, numéro 2 Après un rappel de l'origine digestive et métabolique des acides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 61 publications
1
6
0
1
Order By: Relevance
“…Cow’s milk contains approximately 0.5 µg/L of vitamin B12, while colostrum is four to 10 times more than milk [ 3 ]. It has been shown that the composition and management of the diet in dairy herds can affect the concentration of vitamin B12 in milk, mainly because the ruminal synthesis of vitamin B12 is affected by the diet [ 40 , 64 , 65 ] and because the vitamin is partially secreted by milk [ 66 ]. Furthermore, the variability in the concentration of vitamin B12 between cows could be partly explained by genetic factors [ 40 , 41 ].…”
Section: Cobalt Metabolism: Absorption Storage and Excretionmentioning
confidence: 99%
“…Cow’s milk contains approximately 0.5 µg/L of vitamin B12, while colostrum is four to 10 times more than milk [ 3 ]. It has been shown that the composition and management of the diet in dairy herds can affect the concentration of vitamin B12 in milk, mainly because the ruminal synthesis of vitamin B12 is affected by the diet [ 40 , 64 , 65 ] and because the vitamin is partially secreted by milk [ 66 ]. Furthermore, the variability in the concentration of vitamin B12 between cows could be partly explained by genetic factors [ 40 , 41 ].…”
Section: Cobalt Metabolism: Absorption Storage and Excretionmentioning
confidence: 99%
“…Furthermore, another study using multiparous cows, presented that vitamin B 12 concentration significantly decreased in serum from 5.7 ng/ml at 55 days prepartum to 2.3, 2.0 and 1.9 ng/ml at 20, 7 and 120 days after parturition respectively (Kincaid and Socha 2007 ). Synthesis of B 12 and folic acid in the rumen of dairy cattle has been measured to be 73.0–79.8 and 16.5–21.0 mg/day respectively (Santschi et al 2005 ; Schwab et al 2006 ), and these rates of synthesis significantly affect the amount of vitamins secreted into milk (Ferlay et al 2013 ). Some studies reported that vitamin B 12 deficiency is sometimes mitigated by high folate concentration (Selhub et al 2009 ), and that vitamin B 12 secretion into the milk can be managed in dairy animals through dietary supplementation of vitamin B 12 .…”
Section: Folates and Vitamin B 12 Interactionmentioning
confidence: 99%
“…Par ailleurs, comparativement au pâturage de prairies temporaires, le pâturage de prairies permanentes diversifiées est à l'origine d'une augmentation dans le lait et le fromage de la teneur en acide α-linolénique et d'une réduction de la teneur en acides gras saturés les plus délétères vis-à-vis des maladies cardiovasculaires, notamment l'acide palmitique (Ferlay et al 2013). Les fromages issus des prairies les plus diversifiées présentent également une palette d'arômes plus étendue et une flaveur globale moins intense que les fromages issus de prairies moins diversifiées.…”
Section: / Les Processus Biologiques Sous-jacents Aux Services Rendusunclassified